Intelligent electronic nose system for basal stem rot disease detection - Marni Azira Markom; Ali Yeon, Md Shakaff; Abdul Hamid, Adom; Mohd Noor, Ahmad; Wahyu, Hidayat; Abu Hassan, Abdullah; N., Ahmad Fikrib (Elsevier, 2009)
Link to publisher's homepage at www.elsevier.com